29 Mental health patient-reported outcome measures (PROMs) for children and young people with epilepsy: a systematic review. Issue 12 (14th November 2022) - Pick, Susannah; Aveiro, Bianca De; Winsor, Alice; Simpson, Anna; Nicholson, Timothy; Pal, Deb; Richardson, Mark
Abstract : Objectives/Aims: Children with epilepsy (cwE) are at a higher risk of mental health disorders such as depression, anxiety, and attention deficit hyperactivity disorder (ADHD) compared to the general population. Psychiatric comorbidities can negatively impact cwE as they can be associated with reduced response to treatment, reduced quality of life, as well as increased mortality. Despite the high prevalence and negative impact on cwE, psychiatric comorbidities often go undetected and as a result are not treated. Therefore, it is essential to detect psychiatric comorbidities early in cwE, to facilitate provision of appropriate interventions and improve long-term neuropsychological outcomes. We sought to identify and evaluate child mental health Patient-Reported Outcome Measures (PROMs) that have been validated specifically in children and/or young people with epilepsy, to inform selection of high quality mental health PROMs in paediatric epilepsy settings. Methods: We systematically searched MEDLINE, EMBASE and Psych Info for studies that validated mental health PROMs in paediatric epilepsy samples and assessed methodological quality using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidance. Data on PROM development, structural validity, internal consistency, test-retest reliability, convergent validity and responsiveness were extracted and used to assess the measurement properties with reference to standardised criteria. Results: A total of nine papers were identified that validated 10 mental health PROMs (two epilepsy-specific, eight generic). The overall appraisal of each questionnaire was limited by the availability of only one or two published articles for each PROM. Internal consistency and convergent validity were the more commonly assessed properties across studies, whereas there were very few evaluations of PROM development, structural validity, test-retest reliability, and criterion validity. The strongest performing tool demonstrating the most evidence was The Neurological Disorders Depression Inventory-Epilepsy for Youth (NDDI-Y-E). The ADHD Rating Scale-IV (ADHD-RS-IV) and The Paediatric Symptom Checklist -17 (PSC-17) demonstrated good evidence in favour of at least two measurement properties. Conclusions: This systematic review identified only a small number of validated mental health PROMs for paediatric epilepsy, highlighting the need for further development, validation and evaluation of mental health PROMs in this population.